Measuring entrepreneurship in developing countries - Sameeksha Desai (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
This paper discusses the difficulties associated with measuring entrepreneurship in developing countries. Three important dichotomies in the research on entrepreneurship are discussed: formal-informal, legal-illegal, and necessity-opportunity. Several common measures of entrepreneurship are outlined along with their relevance to developing countries, including self-employment, Global Entrepreneurship Monitor data, World Bank Group Entrepreneurship Survey data and OECD data. The implications of the current understanding of entrepreneurship are discussed with respect to institutions and economic development.
Keywords: L26; O17; O20; 330; entrepreneurship; economic development; data; institutions; Entrepreneurship-Ansatz; Entwicklung; Messung; Entwicklungsländer